The Big Compost Experiment: Using citizen science to assess the impact and effectiveness of biodegradable and compostable plastics in UK home composting - Purkiss, Danielle; Allison, Ayşe Lisa; Lorencatto, Fabiana; Michie, Susan; Miodownik, Mark (Frontiers in Sustainability, 2022)
Compostable and biodegradable plastics are growing in popularity but their environmental credentials need to be more fully assessed to determine how they can be a part of the solution to the plastic waste crisis. We present results and analysis on home compostable packaging. This type of packaging requires the citizen to able to correctly identify the packaging as ‘home compostable’, to have composting facilities at home, and to successfully compost the plastic. Using a citizen science approach, we engaged with 9701 UK citizens geographically spread across the UK to examine their capability, opportunity, and motivation to do this. Of this cohort 1648 citizens performed home compost experiments to test the environmental performance of compostable plastics. We report on the type of plastics they tested and their disintegration under real home composting conditions. The results show that the public are confused about the meaning of the labels of compostable and biodegradable plastics. 14% of sampled plastic packaging items tested were certified ‘industrial compostable’ only and 46% had no compostable certification. Of the biodegradable and compostable plastics tested under different home composting conditions, the majority did not fully disintegrate, including 60% of those that were certified ‘home compostable’. We conclude that for both of these reasons, home composting is not an effective or environmentally beneficial waste processing method for biodegradable or compostable packaging in the UK.